2017
DOI: 10.1093/jamia/ocx091
|View full text |Cite
|
Sign up to set email alerts
|

The representativeness of eligible patients in type 2 diabetes trials: a case study using GIST 2.0

Abstract: Our study quantified the representativeness of multiple type 2 diabetes trials. The common low representativeness of type 2 diabetes trials could be attributed to specific study design requirements of trials or safety concerns. Rather than criticizing the low representativeness, we contribute a method for increasing the transparency of the representativeness of clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…The choice of CV inclusion criteria in CVOTs therefore predefines the trial‐specific baseline CV risk, thereby impacting the representativeness of the trial population compared to a general T2D population . This difference is important, as people with T2D who have, for example, a high CV risk may respond differently to the intervention compared with those with low CV risk, potentially challenging the external validity of results when comparing a trial population with a general T2D population …”
Section: Inroductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of CV inclusion criteria in CVOTs therefore predefines the trial‐specific baseline CV risk, thereby impacting the representativeness of the trial population compared to a general T2D population . This difference is important, as people with T2D who have, for example, a high CV risk may respond differently to the intervention compared with those with low CV risk, potentially challenging the external validity of results when comparing a trial population with a general T2D population …”
Section: Inroductionmentioning
confidence: 99%
“…7 This difference is important, as people with T2D who have, for example, a high CV risk may respond differently to the intervention compared with those with low CV risk, potentially challenging the external validity of results when comparing a trial population with a general T2D population. 23,24 We present a novel way of evaluating the external validity of CVOT results (DECLARE-TIMI 58) in an observational setting, by both using similar main CV inclusion criteria to define a population (DECLARE-likepopulation), and by assessing identical trial-specific outcomes (HHF or CV mortality, and major adverse CV events [MACE]). 5 To our knowledge, no observational study assessing an SGLT2 inhibitor and its associations with CV risk has previously investigated the external validity of CVOT results by applying the same CV inclusion criteria to a general T2D population and assessing identical outcomes.…”
mentioning
confidence: 99%
“…Many CVOTs include patients with a high risk of CV and with an expected high rate of CV events, to ensure that differences in CV outcomes may be reported with sufficient statistical power. As a consequence, various degrees of strict CVOT patient enrolment criteria may impact the representativeness of the trial population of a general T2D population and, thus, may also impact the external validity of study results …”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, various degrees of strict CVOT patient enrolment criteria may impact the representativeness of the trial population of a general T2D population and, thus, may also impact the external validity of study results. 8,9 Four CVOTs that examined treatment with SGLT-2is are within the scope of this study. [3][4][5][6] Major differences exist among these CVOTs concerning inclusion criteria.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a previous literature review, the external validity of large trials assessing the impact of glycaemic control on CVD in patients with T2D was reported as limited when applied to a T2D population-based cohort [27]. Another recent study evaluated the population representativeness of 1691 registered T2D trials [28] and found that in 51.4% of cases (and 53.1% of phase 2 and 3 interventional trials), the population representativeness was <5%. Of note, and in line with our results, the eligibility criterion that had the largest effect on the population representativeness was HbA1c [28].…”
Section: Discussionmentioning
confidence: 99%